Analisis Pengaruh Kinerja Keuangan Terhadap Tanggung Jawab Sosial Perusahaan (Corporate Social Responsibility) Pada Bank Bumn Di Indonesia (Studi Pada Bank Bumn Periode 2010-2019) - Wulan Setyo Rini; M Agus Salim; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThe purpose of this study was to analyze the effect of financial performance on the social responsibility of banking companies, especially state-owned banks in Indonesia. The research object is all state-owned banks in Indonesia for the period 2010-2019. The data used are secondary data in the form of financial reports from each bank. The independent variable is financial performance (size, profitability and leverage), while the dependent variable is corporate social responsibility. Data analysis used multiple linear regression analysis. The results of this study indicate that size and profitability have an effect on corporate social responsibility at state-owned banks, while leverage has no effect on corporate social responsibility at state-owned banks in Indonesia.Keywords: Size, profitability, leverage, Corporate Social Responsibility